The Natural Right To Parody: Assessing The (Potential) Parody/Satire Dichotomies In American And Canadian Copyright Laws - Lai, Amy (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2018)
This paper argues that the right to expressing oneself through parodies should constitute part of the core freedom of expression of a normative copyright regime. By drawing upon natural law legal theories, the paper proposes a legal definition of parody that would help to bring the copyright jurisprudence of a jurisdiction more in line with its free speech tradition. It argues that a broad parody definition, one that encompasses a great variety of expressive works but would not compete with the original and its derivatives in the market, is preferable to a narrow one. The paper then explains why the parody defence in American law and the parody exception in the Canadian copyright statute should follow the proposed parody definition, which would properly balance the rights of copyright owners with those of users.